Lovers Versus Rivals: The Manifestation of Jealousy in the Amorous Verse of Mirza Ghalib and John Donne - Muhammad Asif Khan; Ghulam Murtaza (بازیافت, 2018)
Mirza Ghalib and John Donne are regarded as prominent love poets of their respective languages. Their treatment of the theme of love, i.e., romantic love, is quite realistic and unconventional. Jealousy is an important aspect of the emotion of romantic love. The present study explores various sources of jealousy as they are experienced by the protagonists, the male lovers in the poetry of Donne and Ghalib. One of these sources of jealousy is the presence of the Rival. The study discusses the impact of the presence of the Rival on the love triangles of Donne and Ghalib and illustrates how lovers in them react to the power and influence of the Rival. The study takes insights from the social sciences, as for example the concept of sexual jealousy given by Berscheid & Regan (2005 ) and applies them to the love poetry of Donne and Ghalib. The present is a case study of comparative literature and analyses the various manifestations of the emotion of jealousy in the love poetry of Donne and Ghalib in order to determine how much these love poets from two different cultures and times resemble with or differ from each other.